Tailored outreach communications for farmers in Guatemala and Mexico - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We designed more tailored communications mechanisms, and we successfully pilot them in three regions: the Central-South region (7 departments) and in the El Progreso department in Guatemala, and Chiapas state in Mexico.